The relationship between biofilm formation, genes of virulence and iron metabolism in Escherichia coli - Handrová, Lívia; Čuvalová , Anna; Kmeť , Vladimír (Annales Universitatis Paedagogicae Cracoviensis Studia Naturae, 2018)
Escherichia coli is known as one of the bacterial species with the widest adaptability to variety of niches either within organisms or outside in environment. Most strains of E. coli are of low virulence and associated with opportunistic infections, whereas others are highly virulent. The success of E. coli in colonising such a wide range of hosts and environments is basically due to a noticeable ductility in exploiting the available resources. It is becoming increasingly clear that biofilms have an enormous impact on medicine because since 65% of animal and human bacterial infections involve biofilms. In present study, we isolated strains of E. coli from animals. 19 interesting isolates were selected and tested by PCR amplification to virulence - iutA, cvaC, iss, tsh, papC, kps, iha and iron metabolism genes - sitA, feoB, irp2, fyuA, iroN, ireA. The ability of biofilm formation was assessed in a quantitative assay using a microtiter-plate test. Bacterial strains were grown on BHI. We divided isolates of E. coli into four classes: very weak (63.0%), weak (10.5%), moderate (10.5%) and strong (16.0%) biofilm producers. Representation genes of virulence were highly in isolates from very weak biofilm producers - from 7 genes were 6 highly; only papC (P fimbrial adhesin) was low. Genes of iron metabolism were different. Genes - sitA, fyuA, ireA in strong isolates producing biofilm and feoB, irp2, iroN in weak producers were most represented. The results show possible relation between presence virulence factor and low biofilm formation.